1999
DOI: 10.1161/01.hyp.33.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

The 825C/T Polymorphism of the G-Protein Subunit β3 Is Not Related to Hypertension

Abstract: Abstract-A polymorphism at position 825 (C3 T) of the cDNA that encodes the ␤3 subunit (GNB3) of the pertussis toxin-sensitive G protein was recently shown to be associated with human hypertension. To verify this finding and to investigate whether this polymorphism could also be associated with coronary heart disease, we analyzed the GNB3 variant in subjects from 2 previously described studies: Projet d'Etude des Gènes de l'hypertension Artérielle Sévère à modérée Essentielle (PEGASE), a case-control study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
6
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 18 publications
2
64
6
2
Order By: Relevance
“…36 Published studies on the possible influence of the GNB3 C825T polymorphism reported inconsistent results. The 825T allele was associated with increased blood pressure [40][41][42] or increased risk of hypertension 22,43,44 in Germans, 22,39,42,44 Australian White hypertensive patients 41 and Caribbean or West African Blacks, 43 but not in French, 22 Irish, 22 Japanese 45,46 or African Americans. 47 These discordant findings suggest that ethnic or genetic background, 8 lifestyle or various environmental factors may modulate the potential effect of the C825T allele on blood pressure.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…36 Published studies on the possible influence of the GNB3 C825T polymorphism reported inconsistent results. The 825T allele was associated with increased blood pressure [40][41][42] or increased risk of hypertension 22,43,44 in Germans, 22,39,42,44 Australian White hypertensive patients 41 and Caribbean or West African Blacks, 43 but not in French, 22 Irish, 22 Japanese 45,46 or African Americans. 47 These discordant findings suggest that ethnic or genetic background, 8 lifestyle or various environmental factors may modulate the potential effect of the C825T allele on blood pressure.…”
Section: Discussionmentioning
confidence: 92%
“…From the published DNA sequence of the GNB3, 20 we amplified a 268 base pair fragment incorporating the polymorphic site with the use of two primers as described by Siffert et al 21 We previously published the technical procedures, which we implemented for DNA amplification and determination of the genotypes by allele-specific hybridization. 22 …”
Section: Determination Of the Genotypementioning
confidence: 99%
“…Several groups have reproduced the original finding that the GNB3 825T allele is associated with hypertension, whereas other groups refuted that finding Schunkert et al 1998;Benjafield et al 1998;Brand et al 1999;Dong et al 1999, to cite but a few). The fact that there is a considerable variance in genotype distribution within different ethnicities (Siffert et al 1999) creates a major problem.…”
Section: Genetic Variants In the Gene For The Gα Subunit (Gnas) And Tmentioning
confidence: 99%
“…In addition, the early studies in Caucasian populations have demonstrated that a distribution of the C825T genotypes among subjects of European origin ensures appropriate epidemiological representation of each variant in population samples of different size. [6][7][8] …”
mentioning
confidence: 99%
“…In addition, the early studies in Caucasian populations have demonstrated that a distribution of the C825T genotypes among subjects of European origin ensures appropriate epidemiological representation of each variant in population samples of different size. [6][7][8] In light of these findings, a selection of this candidate by Olszanecka et al 9 in their study on genetic determinants of cardiovascular phenotypes is fully justified. They examined associations of the C825T polymorphism with blood pressures as well as indicators of left ventricular structure and function in two generations of Caucasian families.…”
mentioning
confidence: 99%